Evaluating COVID-19 vaccine acceptance among parents in Saudi Arabia: a systematic review examining attitudes, hesitancy, and intentions - Sayed, Anwar A. (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic, affecting adults and children equally, has caused significant disruption to countries worldwide, including Saudi Arabia. In Saudi Arabia, the fast preventative measures and mass vaccine enrollment were vital to contain the devastating impact of the pandemic. However, vaccine hesitancy, especially among parents toward vaccinating their children, was a significant obstacle to vaccine uptake. Methods This systematic review followed PRISMA guidelines to assess parental willingness to vaccinate their children against COVID-19, determine the key determinants influencing such intention and attitudes, and underline the significant concerns and misconceptions regarding the vaccine among parents. The Joanne Briggs Institute (JBI) checklist for prevalence studies was used to assess included studies for risk of bias. Results Twenty-three studies were included in this systematic review, representing a total of 20,926 participants, with over 66% of them were female. Over 37% of the participants were willing to vaccinate their children against COVID-19. Parents’ age, gender, level of education, and income were the main determinants of their intention to vaccinate their children. The parents’ main concerns were the potential vaccine side effects, safety, and efficacy. Major misconceptions about the COVID-19 vaccine included it being dangerous to children and that children are at lower risk of severe infection; hence, vaccines were not needed. Discussion This seminal review provides insights to public health policymakers, which should be considered and taken together in light of other studies addressing parental vaccine hesitancy.